A note on the estimates of multivariate Gaussian probability. Issue 5 (3rd March 2016) - Lu, Dawei
ABSTRACT: Some lower and upper bounds of multivariate Gaussian probability are given based on the univariate Mills' ratio. These bounds are sharper than known ones on the multivariate Mills' ratio in many case.